2011
DOI: 10.1111/j.1939-3938.2011.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

An examination of SANE data

Abstract: The current study analyzes adult female sexual assault data, collected by sexual assault nurse examiners (SANEs) in New Hampshire, United States, between 1997 and 2007. The purposes of this study were to (1) explore the relationship between patient and assailant, (2) examine patients' physical findings according to assailant type, (3) describe characteristics of both the patients and the assaults, and (4) make care recommendations. Secondary analysis was conducted on data gathered by SANEs from responses to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In this study, relatives comprised the majority of perpetrators in all age groups, with 62% of the 2 to 5 year old group experiencing CSA by a relative compared to 33% by an acquaintance. A similar finding was reported by Murphy et al (2010); for children younger than 6 years old; 44% of perpetrators were relatives compared to 3 8% acquaintances.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In this study, relatives comprised the majority of perpetrators in all age groups, with 62% of the 2 to 5 year old group experiencing CSA by a relative compared to 33% by an acquaintance. A similar finding was reported by Murphy et al (2010); for children younger than 6 years old; 44% of perpetrators were relatives compared to 3 8% acquaintances.…”
Section: Discussionsupporting
confidence: 73%
“…The vast majority of children in this study knew their perpetrators, which is widely documented in the literature (Douglas & Finkelhor, 2005;Murphy et al, 2010). Studies estimate that 50% of perpetrators are acquaintances; the estimate for relatives is more disparate (14% to 47%) (Douglas & Finkelhor, 2005;Murphy et al, 2010). In this study, relatives comprised the majority of perpetrators in all age groups, with 62% of the 2 to 5 year old group experiencing CSA by a relative compared to 33% by an acquaintance.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Very few studies explore the characteristics associated with acquaintance sexual assault. The ones that do often find that acquaintance sexual assault victims are younger (Logan et al, 2007;Stermac et al, 2001), they are more likely to be under the influence of drugs and/or alcohol at the time of the assault (Logan et al, 2007;Moller et al, 2012;Stermac et al, 2001), and they are more likely to seek help within 24 hours of the assault when compared to intimate partner sexual assault victims (Murphy et al, 2011). In a study using data from 331 women who sought treatment in an emergency room between 2001 and 2004, Logan et al (2007) found that acquaintances were more likely to experience non-genital injuries when compared to victims who had recently met (within 24 hours) their assailant but not when compared to stranger or intimate partner sexual assault victims.…”
Section: Characteristics Of Acquaintance Sexual Assaultmentioning
confidence: 99%